Intercultural Communicative Language Teaching in China: Highlight or Addendum? - WANG, QUN; Syihabuddin, Syihabuddin; Mulyati, Yeti; Damaianti, Vismaia Sabariah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractInternational students were frequently reported of culture shock issues when entering a new cultural environment. Cultural knowledge was often treated as an addendum which focused on learning facts about the target country. This article demonstrated culture shock that experienced by 7 international students, and also reviewed intercultural communicative language teaching (ICLT) in Indonesian language classrooms practiced by 6 language practitioners from 3 different universities in China. Using findings that emerged from a series of one-to-one interviews, the research explored practitioners’ current perspective of ICLT and how these understandings influenced their practices, including teaching materials, methods, and activities. The researcher discussed the possible causes of the status quo of ICLT in China, and went on to put forward suggestions that ICLT should be promoted in foreign language teaching as a successful mediator of intercultural dimension.AbstrakMahasiswa internasional sering dilaporkan tentang masalah kejutan budaya ketika memasuki lingkungan budaya baru. Pengetahuan budaya sering diperlakukan sebagai tambahan yang berfokus pada mempelajari fakta tentang negara sasaran. Artikel ini menunjukkan kejutan budaya yang dialami oleh 7 siswa internasional, dan juga mengulas pengajaran bahasa komunikatif antarbudaya (ICLT) di ruang kelas bahasa Indonesia yang dipraktikkan oleh 6 praktisi bahasa dari 3 universitas berbeda di Tiongkok. Menggunakan temuan yang muncul dari serangkaian wawancara satu-ke-satu, penelitian mengeksplorasi perspektif praktisi saat ini tentang ICLT dan bagaimana pemahaman ini mempengaruhi praktik mereka, termasuk bahan ajar, metode, dan kegiatan. Peneliti membahas kemungkinan penyebab status quo ICLT di Cina, dan kemudian mengajukan saran bahwa ICLT harus dipromosikan dalam pengajaran bahasa asing sebagai mediator sukses dimensi lintas budaya. How to Cite :, Wang, Q., Syihabuddin., Mulyati, Y., Damaianti, V. S. (2018). Intercultural Communicative Language Teaching in China: Highlight or Addendum?. TARBIYA: Journal of Education in Muslim Society, 5(2), 155-165. doi:10.15408/tjems.v5i2.9732.